A Theoretical Evaluation of Smart Production Systems and Industrial Robots within the Context of Industry 4.0 - Akıllıoğlu, Faika Selcen (Zenodo, 2025)
This study comprehensively addresses the role of intelligent manufacturing systems, industrial robots, and dark factories in production processes and the transformation process brought about by Industry 4.0. Today, manufacturers are pressured to produce higher-quality products with shorter lead times. This requirement has necessitated that production systems become integrated, automated, and intelligent. Smart manufacturing creates flexible, responsive and highly efficient production environments using artificial intelligence (AI), internet of things, big data analytics and robotics. Industrial robots have become systems that can not only act on a task basis but also learn, predict, and actively participate in production processes by interacting with humans. In this direction, dark factories are facilities that can produce 24 hours a day without human intervention and offer significant advantages regarding occupational safety, quality and efficiency. However, there are difficulties in the widespread use of these systems, such as high investment costs, applicability limitations in some sectors and the decreasing need for unskilled labour. In conclusion, for the technological opportunities offered by Industry 4.0 to provide sustainable and inclusive benefits, investments incompetent human resources should be increased, education policies should be restructured, and strategic public support should be activated.